2014
DOI: 10.1186/s12302-014-0032-3
|View full text |Cite
|
Sign up to set email alerts
|

Microinjection into zebrafish embryos (Danio rerio) - a useful tool in aquatic toxicity testing?

Abstract: Background: Microinjection was tested as a potentially powerful tool to introduce natural and anthropogenic pollutants directly into fish eggs to determine their toxicological impact on fish. With this technique, parental transfer of lipophilic contaminants may be mimicked. Here, we investigated the applicability of pollutant injection into the yolk of early zebrafish (Danio rerio) eggs with special regard on survival after vehicle injection. Tested vehicles were autoclaved tap water, dimethyl sulfoxide (DMSO)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 43 publications
(76 reference statements)
1
28
0
2
Order By: Relevance
“…Neither canola oil nor DMSO affected any of the toxicity endpoints. Dimethylsulfoxide has already been used for the injection of zebrafish embryos in previous studies (Maes et al ; Schubert et al ; Li et al ), but triolein is the more commonly used solvent in injection studies with fish embryos (Edmunds et al ; Hano et al ; Nassef et al ; Schubert et al ; Xiao et al ). Our results, however, showed that the use of triolein can lead to effects on survival and heart rate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Neither canola oil nor DMSO affected any of the toxicity endpoints. Dimethylsulfoxide has already been used for the injection of zebrafish embryos in previous studies (Maes et al ; Schubert et al ; Li et al ), but triolein is the more commonly used solvent in injection studies with fish embryos (Edmunds et al ; Hano et al ; Nassef et al ; Schubert et al ; Xiao et al ). Our results, however, showed that the use of triolein can lead to effects on survival and heart rate.…”
Section: Discussionmentioning
confidence: 99%
“…Out of these 2 potential solvents, DMSO was selected as the optimal solvent for the present study because the high viscosity of canola oil caused practical problems. In addition, DMSO has already been used in similar micro-injection studies with zebrafish (Maes et al 2012;Schubert et al 2014;Li et al 2015). The variation among 3 different injection needles and within a single injection needle (3 replicates) is shown in Figure 2B.…”
Section: Optimization and Evaluation Of Technical Aspects Of The Micrmentioning
confidence: 99%
See 2 more Smart Citations
“…Although, microinjection of substances into the yolk of zebrafish eggs is feasible, introduction of accurate volumes (e.g. constant volumes) through a series of injections seems to be problematic so nominal and real injected volumes may be different (Schubert et al, 2014).…”
Section: Introductionmentioning
confidence: 99%